Nucleoside Modifications (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
This book contains a collection of twelve state-of-the-art, original papers with results from contemporary research in the syntheses and uses of nucleosides and nucleoside analogues, as well as two reviews on contemporary methodology to modify nucleosides.